Pengaruh Work From Home, Gaya Kepemimpinan Situasional Dan Motivasi Kerja Terhadap Kinerja Karyawan Di Perumda Pasar Argha Nayottama Kabupaten Buleleng - I Kadek Satria Wibawa; Ni Wayan Novi Budiasni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study has the aim of knowing the effect of work from home, situational leadership style and work motivation on the performance of employees of the Argha Nayottama Market Pasar Buleleng Regency. The analysis used is the validity and reliability test, linear regression analysis, classical assumption test, T-test, F-Test test and determination analysis. This study shows that work from home, situational leadership styles and work motivation have a significant positive effect on the performance of the employees of the Argha Nayottama Market, Buleleng Regency. So it is important for related parties to consider the factors of work from home, situational leadership styles and work motivation to improve the performance of its employees.